Synthesis of stilbenes for potential application as photoacid generators in polymer film modification / Lee Jia Yin - Lee, Jia Yin (2015)
Photo-acid generators (PAGs) are significant components for photolithography, required for polymer thin film modification in the semiconductor industry. Upon UV irradiation through a photomask, a PAG is photolysed liberating a photoacid that catalytically reacts with a photoresist polymeric matrix either by hydrolysing the polymer or by cross linking the monomers that later affects the solubility of the photoresist in an alkaline developer. Stilbenes with suitable ortho-substituents are known to undergo photocyclisation upon UV irradiation with subsequent dehydrogenation yielding phenanthrene and an acid. A series of halogenated and tosylated ortho-substituted stilbenes were synthesized by employing the Wittig reaction of ortho-substituted aryl aldehydes with benzyl triphenylphosphonium ylide, or, via the modified Perkin-Aldol reaction of ortho-substituted aryl aldehydes with phenyl acetic acid. The selected halogens (Br, Cl) and tosyloxy group (OTs) are good leaving groups thus enhancing the photolysis reaction that liberates Bronsted acids. The afforded compounds via modified Perkin Reaction were then esterified to obtain the α-substituted methyl ester stilbenes that predominantly gave E-isomers. The synthesized compounds were purified by various chromatographic methods (thin layer chromatography, column chromatography, centrifugal thin layer chromatography and Sephadex LH-20), and characterized by 1H NMR, 13C NMR and HR-DART-MS. Thus the structures of the synthesized stilbenes were firmly established. It was observed that the yields obtained when employing the Wittig reaction ranges from 30-50 %, while the yields obtained using the modified Perkin-Aldol reaction was generally lower, from 20-40 %.